SELF-ASSESSMENT ON INDONESIAN EFL STUDENTS' WRITING COMPETENCES - Aminatus Sa’diyah; Slamet Setiawan; Tengsoe Tjahjono; Syafi’ul Anam (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2021)
Abstract: The objective of the study is to enhance students' ability to write English teachings through self-assessment. The method is applied with a group design for the pre-and post-test analysis. The study population in this study is the tenth graders of EFL students in Gresik. However, 30 students are used as a purposeful sampling method for the study of this analysis. The tools for this analysis have been tested. The data were obtained before and after the tests. The findings of pre-test and post-test have been analyzed by an SPSS 16.00 t paired sample test (0.000 < 0.05). The findings found that the implementation of self-assessment boost students’ writing ability. Therefore, the conclusions of this study were accepted. There was a significant improvement in students' writing ability by using self-assessment. The usage of self-assessment can be inferred as increasing the students' writing skills.Keywords: Self-Assessment – Writing – EFL